Characterization of flil proteins in bradyrhizobium diazoefficiens: Lateral FLIL supports swimming motility, and subpolar FLIL modulates the lateral flagellar system - Mengucci, Florencia (2019)
Bradyrhizobium diazoefficiens is a soil alphaproteobacterium that possesses two evolutionarily distinct flagellar systems, a constitutive subpolar flagellum and inducible lateral flagella that, depending on the carbon source, may be expressed simultaneously in liquid medium and used interactively for swimming. In each system, more than 30 genes encode the flagellar proteins, most of which are well characterized. Among the exceptions is FliL, which has been scarcely studied in alphaproteobacteria and whose function in other bacterial classes is somewhat controversial. Because each B. diazoefficiens flagellar system contains its own fliL paralog, we obtained the respective deletions ΔfliLS (subpolar) and ΔfliLL (lateral) to study their functions in swimming. We determined that FliLL was essential for lateral flagellum-driven motility. FliLS was dispensable for swimming in either liquid or semisolid medium; however, it was found to play a crucial role in upregulation of the lateral flagellum regulon under conditions of increased viscosity/flagellar load. Therefore, although FliLS seems to be not essential for swimming, it may participate in a mechanosensor complex that controls lateral flagellum induction.